2019
DOI: 10.3390/s19173687
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Dust Storms in Iraq Using Satellite Data

Abstract: Dust storms can suspend large quantities of sand and cause haze in the boundary layer over local and regional scales. Iraq is one of the countries that is often impacted to a large degree by the occurrences of dust storms. The time between June 29 to July 8, 2009 is considered one of the worst dust storm periods of all times and many Iraqis suffered medical problems as a result. We used data from the Moderate Resolution Imaging Spectroradiometer (MODIS). MODIS Surface Reflectance Daily L2G Global 1km and 500m … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 43 publications
(63 reference statements)
0
5
0
Order By: Relevance
“…This paper reveals fine agreement among satellite revelation and In-situ data. Researcher presented that NDDI and TB have preferential threshold over study area on the contrary with the former studies [30]. Mohsin Jamil Butt illustrate that the effect of wind blow from the desert and carried sand and dust have a prime regard for the ecology system and climate studies because of their due to their international scope.…”
Section: Introductionmentioning
confidence: 86%
“…This paper reveals fine agreement among satellite revelation and In-situ data. Researcher presented that NDDI and TB have preferential threshold over study area on the contrary with the former studies [30]. Mohsin Jamil Butt illustrate that the effect of wind blow from the desert and carried sand and dust have a prime regard for the ecology system and climate studies because of their due to their international scope.…”
Section: Introductionmentioning
confidence: 86%
“…Another physicist assessed the effect of dust pollution on the efficiency of solar arrays in Saudi Arabia. The experiment out showed that the buildup of sand from the desert over eight months resulted in a 32% loss in electricity generated [28]. Similarly, sand deposition in Kuwait resulted in a 17% decrease in the energy efficiency of PV modules in just six days, according to research [29].…”
Section: Literature Reviewmentioning
confidence: 96%
“…At present, the relevant studies mainly focus on the wind-blown sand hazards of traffic engineering and blown sand environmental monitoring. These focuses include wind-induced fatigue and asymmetric damage in bridges [ 9 ], buffeting response analysis of bridges [ 10 ], wind-blown sand along railway infrastructures and mitigation measures thereof [ 11 ], remote measurement of aeolian sand transport on sandy beaches and dunes [ 12 ], satellite monitoring of dust storms [ 13 ], the law of sand particle accumulation over railway subgrade [ 14 ], estimation methods and techniques of aeolian sand transport rate [ 15 ], sand dune ridge alignment effects on the surface [ 16 ], damage by wind-blown sand and its control measures along desert highways [ 17 ], wireless wind data acquisition systems at arid coastal foredunes [ 18 ], and wind speed forecasting in traffic control decision support systems [ 19 ]. However, these studies focus on the form of a single highway and railway line, and systematic studies are lacking on the environmental effects of blown sand in the form of subgrades and bridges.…”
Section: Introductionmentioning
confidence: 99%